Successful cardiopulmonary resuscitation of cardiac arrest induced by massive pulmonary embolism under general anesthesia: a case report - Li, Zhen; Cai, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background While pulmonary embolism (PE) is a common occurrence, a large life-threatening PE is not. Herein, we discuss the case of a patient with a life-threatening PE that occurred under general anesthesia. Case presentation We present the case of a 59-year-old male patient who was at bed rest for several days due to trauma, which resulted in femoral and rib fractures and a lung contusion. The patient was scheduled for femoral fracture reduction and internal fixation under general anesthesia. After disinfection and surgical towel laying, there was a sudden occurrence of severe PE and cardiac arrest; the patient was successfully resuscitated. Computed tomography pulmonary angiography (CTPA) was performed to confirm the diagnosis, and the patient’s condition improved after thrombolytic therapy. Unfortunately, the patient’s family eventually discontinued treatment. Discussion Massive PE frequently occurs suddenly, may endanger a patient’s life at any point in time, and cannot be diagnosed quickly on the basis of clinical manifestations. Although the vital signs fluctuate greatly and there is insufficient time to conduct more tests, some factors such as special disease history, electrocardiography, end-tidal carbon dioxide, and blood gas analysis may help us determine the preliminary diagnosis; however, the final diagnosis is made using CTPA. Current treatment options include thrombectomy, thrombolysis, and early anticoagulation, of which thrombolysis and early anticoagulation are the most feasible. Conclusion Massive PE is a life-threatening disease that requires early diagnosis and timely treatment to save patients’ lives.